2011
DOI: 10.4067/s0718-18762011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Comprehensive Patent Related Information Retrieval Tool

Abstract: In recent years, there has been a massive growth of regulatory and related information available online. This information is distributed across many different domains creating a problem for accessing and managing this data. This paper proposes a framework to access information across two such domains -patents and court cases. The framework is designed to boost the value of a set of patents based on information available in court cases by identifying and cross-referencing mutual information in the two domains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The tool has the potential to identify objectively what agencies are involved in the management of a topic across sectors and levels of government. In a collaborative effort with Prof. Jay Kesan at University of Illinois, our research has been extended to deal with laws and regulations related to intellectual properties (IP) [36,37]. Information pertaining to IP includes not only laws and regulations, but also patents, court cases, scientific literature, and other related data.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The tool has the potential to identify objectively what agencies are involved in the management of a topic across sectors and levels of government. In a collaborative effort with Prof. Jay Kesan at University of Illinois, our research has been extended to deal with laws and regulations related to intellectual properties (IP) [36,37]. Information pertaining to IP includes not only laws and regulations, but also patents, court cases, scientific literature, and other related data.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The techniques developed will account for varying language and make maximum utilization of the cross-referenced information [39], [40]. The required domain knowledge is available in the form of bioontologies at BioPortal.…”
Section: A Future Workmentioning
confidence: 99%
“…Domain ontologies provide a rich source of knowledge allowing applications to understand the semantics of the domain and handle terminological inconsistencies. For information retrieval, the use of domain knowledge can enhance the quality of results obtained [13,14]. In this paper, we present our methodology based on documents in the biomedical domain.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have shown that the use of domain ontologies in IR facilitates semantic inter-operability and improves the quality of the results [11,13,14]. Another approach to handle terminological inconsistencies is Latent Semantic Indexing (LSI), where the various terms are mapped onto a single concept axis [28].…”
Section: Introductionmentioning
confidence: 99%